2017
DOI: 10.1002/cbin.10755
|View full text |Cite
|
Sign up to set email alerts
|

Androgen regulation of host defenses and response to inflammatory stimuli in the prostate gland

Abstract: The prostate gland is a strictly androgen-dependent organ which is also the main target of infectious and inflammatory diseases in the male reproductive tract. Host defenses and immunity of the gland have unique features to maintain a constant balance between response and tolerance to diverse antigens. In this context, the effects of reproductive hormones on the male tract are thus complex and have just started to be defined. From the classical description of "the prostatic antibacterial factor," many host def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 125 publications
(182 reference statements)
0
6
0
Order By: Relevance
“…The ability of androgens to promote anti-inflammatory/immunomodulatory phenotypes has been previously recognized for professional immune cells ( 16 , 20 ). In general, testosterone tends to inhibit pro-inflammatory molecules such as TNFα, iNOS, and NO whereas induces IL10 and TGFβ1 anti-inflammatory signaling ( 19 , 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of androgens to promote anti-inflammatory/immunomodulatory phenotypes has been previously recognized for professional immune cells ( 16 , 20 ). In general, testosterone tends to inhibit pro-inflammatory molecules such as TNFα, iNOS, and NO whereas induces IL10 and TGFβ1 anti-inflammatory signaling ( 19 , 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in monocytes/macrophages, androgens reduce proinflammatory signaling (TLR4, TNFα, IL1β, and IL6) ( 18 ) but enhance anti-inflammatory (IL10) cytokine production ( 19 ). Regarding innate immunity, a few published articles have suggested that testosterone maintains a reduced expression of key elements such as TLRs and modulates the activity of different professional cells ( 18 , 20 ). Nevertheless, the influence of androgen levels on neutrophil activity and plasticity in the initial inflammatory response remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Like the seminal vesicles, the prostate is a strictly androgen-dependent organ. Testosterone possesses immunosuppressive properties and influences the innate immune responses as well as the outcome of infections and inflammation in the prostate (564). Thus, in rodents and other animals, castration is efficient at eliminating bacterial pathogens and dampening infectionrelated inflammation of the prostate (564).…”
Section: Immune Characteristicsmentioning
confidence: 99%
“…MLT seemed to present a more effective anti‐inflammatory action under hyperglycemic condition, this can be related to the increased uptake of MLT by prostate cells incubated with hyperglycemic medium observed by Hevia et al (). The influence of alterations in androgens levels on the inflammatory response of prostate gland cannot also be discarded (Quintar and Maldonado, ).…”
Section: Discussionmentioning
confidence: 99%